PERSENTASE SERANGAN HAMA Scirpophaga innotata Wlk PADA BEBERAPA VARIETAS TANAMAN PADI SAWAH DI DESA MOPUYA SELATAN KABUPATEN BOLAANG MONGONDOW - Virginia V. Manoppo; Max Tulung; Noni N. Wanta (Universitas Sam Ratulangi, 2022)
ABSTRACT Rice (Oryza sativa L.) is one of the most important food crops for the Indonesian population because it is a high-carbohydrate staple food. White rice stem borer (Scirpophaga innotata Wlk) is one of the plant pest organisms (OPT) that attacks lowland rice plants in Indonesia and has caused significant losses both qualitatively and quantitatively because this pest attacks rice plants at all stages of plant growth. from nursery to harvest. This study aims to determine the percentage of S. innotata attacks on several varieties of rice plants in Mopuya Selatan Village, Bolaang Mongondow Regency. The research method used is a survey method in the rice field area in the generative phase in one village with three different locations measuring one (1) hectare each and each location making five (5) sub-plots measuring 10 meters x 20 meters, In each subplot 150 clumps of plants were taken using a systematic random method (zigzag). Based on the results of the research conducted, the average percentage of S. innotata pests on the Serayu variety was 41.5%, the Siam-Siam variety was 43.0%, and the Inpari-9 variety was 38.2%. Based on the research that has been done, it can be concluded that the highest percentage of S. innotata attack on the Siam-siam variety was 43.0%, followed by the Serayu variety at 41.5%, and the Inpari-9 variety at 38.2%. In accordance with the results of the study, it can be suggested to do a pattern of varietal rotation to reduce the percentage of S. innotata pests in order to get maximum yields. Key words : Rice paddy (Oryza sativa L.) and Scirpophaga innotata.